Advanced Nanotechnology-Enhanced Delivery Systems for Precision Targeted Herbicide Application in Sustainable Crop Protection - Balassem Zaid Ajzan; Hussein A. H. A.; Ramesh Gajula (SHS Web of Conferences)
Nanotechnology has revolutionized herbicide delivery, which up until now has been a rather crude industry, since it has improved precision and efficiency in agricultural applications. It is in this study that a methodology of developing and optimising delivery systems based on the use of advanced nanomaterials such as Carbon Nanotubes (CNT) and Metal-Organic Frameworks (MOF) is investigated. Controlled release and targeted drug delivery is enabled by herbicide delivery from these materials that are chosen for high surface area and customizable functionalities. Particle Swarm Optimization (PSO) and Finite Element Analysis (FEA) is used to design and fabricate nanocarrier so as to optimize these critical parameters, namely size, shape and surface modification. In predicting system responses in various environments, regression analysis has been applied, and characterizing hydrodynamic diameter and colloidal stability has been performed using Dynamic Light Scattering (DLS). Optimized nanocarrier systems also improved greatly (a 90.5% release efficiency, a controllable biodégradation form of 2.5% per day, and 85.2%) encapsulation efficiency). This papers demonstrates the advancements of herbicide stabilization and release that may be a valuable approach to minimize environmental impacts while defending crops. As this study would demonstrate, introduction of nanotechnology offers an opportunity to combine with computational techniques to produce efficient and eco-friendly agricultural practices.